Potential and characterization biogas from tofu liquid waste with addition cow dung and effective microorganisms 4 as biocatalyst. (2021) - Nurjuwita, Wideawati; Sasongko, Ashadi; Hartanto, Tan Jeremy; Purwanto, Mochammad
Abstract: Energy is a source that needed by human life and cannot be separated. Fossil fuel has historically been the world's most used energy source. However, the source of energy from fossil fuels has decreased, so it necessary to develop alternative energy sources. One of the energy sources that can be used is biogas. Organic wastes such as tofu liquid waste (TLW) and cow dung can be used as a source of biogas energy, because these organic wastes are known to have high methane gas content. The purpose of this research is to determine the optimum temperature and pH during the process fermentation of biogas, the content of biogas compounds analyse, the theoretical calorific value of biogas, as well as the BOD, COD, and TSS content of organic waste before and after fermentation process. The biogas production takes place through anaerobic digestion for about 35 days. From the results of this study, the highest CH4 gas content was 90.351%. The result of theoretical biogas calorific value was 50148.932 kJ/kg for HHV and 46908.932 kJ/kg for LHV, temperature conditions in range of 25–30 °C and a pH value in the range of 7.0 to 8.0. Besides producing energy, the organic waste fermentation process can also reduce levels of organic pollutants BOD, COD, and TSS in the liquid waste used. The highest decrease in BOD, COD, and TSS levels were 97.52%; 91.12%; and 91.22%.